Juridical Implications for Officials Making Land Deeds Determined as Perpetrators of the Crime of Embezzlement of Taxes Fees for Acquisition of Land and Building Titles - Yunendar, Brian; Bawono, Bambang Tri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to determine the juridical implications and responsibilities of the PPAT in terms of receiving deposit of tax payments for land and building rights acquisition fees (BPHTB), then link it with an appropriate theory in order to draw conclusions. The method used in this research is the approach method in writing this is normative juridical, the specification of this research is descriptive analytical research. In the case of depositing BPHTB fees, basically it is paid by PPAT clients, but in practice it is often found that many PPATs are trusted by clients to pay BPHTB from their clients. In this regard, laws and regulations do not regulate the authority of a PPAT who makes land deeds to pay tax on the sale and purchase of land from his client. however, if the clients authorize the PPAT concerned to represent paying tax on the sale and purchase of land in the form of BPHTB to the state treasury, then the PPAT concerned basically does not have the authority to carry out the payment. So that there was evasion of BPHTB tax payments to PPAT. For PPATs who commit this abuse of power, the consequences of these actions are that the PPAT must be able to take responsibility and be subject to appropriate criminal sanctions by the panel of judges, namely Article 372 and/or 374 of the Criminal Code and/or Articles 4, 5, 6 of the Republic of Indonesia Act No.8 of 2010 concerning the Crime of Money Laundering and Article 55 paragraph 1 of the Criminal Code.Keywords: Accountability; Authority; Tax